Friction stir welding of ABS-15Al sheets by introducing compatible semi-consumable shoulder-less pin of PA6-50Al. (January 2019) - Kumar, Ranvijay; Singh, Rupinder; Ahuja, IPS
Highlights: Solution for compatibility issues between two dissimilar thermoplastic materials. MFI of ABS and PA 6 was modeled by reinforcement of Al metal powder. Reinforcement of 15% Al in ABS and 50% Al in PA6 resulted in thermally compatibility. Suggested settings are 1200 rpm, 40 mm/min transverse speed and 8 mm pin diameter. Abstract: This study demonstrates the solution for compatibility issues between two dissimilar thermoplastic materials for friction stir welding (FSW) applications. The joints of similar thermoplastic materials possesses good mechanical strength and uniform morphological characteristics but dissimilar thermoplastic are difficult to join as they are having large variation in molecular weight, carbon chain length, melt flow index (MFI) and melting point etc. In the present study, MFI of dissimilar thermoplastics namely: acrylonitrile butadiene styrene (ABS) and polyamide (PA)6 was modeled by reinforcement of Al metal powder for enhancing the material compatibility. Reinforcement of 15% Al metal powder (by weight) to ABS (as ABS-15Al) and 50% to PA6 (as PA-50Al) resulted in the similar MFI range of 11.57 g/10 min and 11.97 g/10 (with similar melting point range) confirmed the enhanced material compatibility with possibilities of sound FSW joints. Twin screw extrusion (TSE) and fused deposition modeling (FDM) were used to prepare the specimens of ABS-15Al and PA6-50Al and FSW was performed on conventional vertical milling setup. Further multi response optimization has been performed for establishing best settings of input process parameters.